Famines and likelihood of consecutive megadroughts in India - Vimal Mishra (Nature Portfolio, 2021)
Abstract Consecutive failures in the summer monsoon rainfall led to widespread and severe droughts with profound implications for agricultural activities in India. However, the likelihood of successive megadroughts in India’s past and future climate remain poorly understood. Using Palmer Drought Severity Index (PDSI) from the Monsoon Asia Drought Atlas (MADA), we show that the major famines that affected millions of people during 1200–2018 were linked with summer monsoon droughts. Four megadroughts covering more than 40% of the country occurred for two consecutive summer monsoon seasons during 1200–2018. The most recent and severe megadrought occurred in 2002–2003. Simulations from the Community Earth System Model (CESM) for the last millennium (850–2005) ensemble (LME) show that the likelihood of two and three-year consecutive megadroughts during the summer monsoon is about 0.7 and 0.3 events per 100 years, respectively. Large ensemble simulations from CESM (CESM-LE) show a decline in the frequency of megadroughts in the future. Summer monsoon megadroughts are strongly associated with the warm sea surface temperature (SST) anomalies over the Pacific Ocean in the past and future climate. Substantial warming under the projected future climate can cause megadroughts under near-normal precipitation during the summer monsoon season. Despite the projected decline in the likelihood of the summer monsoon megadroughts under the warming climate, megadroughts in the future can have considerable implications for India’s food production and water availability.